2012
DOI: 10.1111/j.1365-2389.2012.01497.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of non‐crystalline minerals in the total amount, resilience and molecular composition of the organic matter in volcanic ash soils (Tenerife Island, Spain)

Abstract: The influence of short‐range ordered minerals, especially allophane or ferrihydrite, in the total amount, resilience and molecular structure of the soil organic matter (SOM) was determined in a series of volcanic ash soils from Tenerife Island (Spain), with a range of amorphous minerals, organic carbon (C) and clay minerals. Up to 120 main analytical descriptors of the SOM were processed by uni‐ and multivariate statistical analyses. Short‐range ordered minerals were estimated from the (Alo + ½ Feo) index, org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Tonneijck et al () found that volcanic soils of the Andes had about twice as much carbon as previously thought and that a significant proportion was stabilized as aluminium (Al)‐complexes. The latter mechanism was also found by Iamarino & Terribile () in Andic soils of the Italian mountains and by Hernández et al () in the soils of Tenerife. However, Scheel et al () attributed the decrease in C mineralization upon increase in soil Al concentration in forest soils to the reduced bioavailablity of C caused by precipitation rather than any toxic effect of the Al at low pH.…”
supporting
confidence: 74%
“…Tonneijck et al () found that volcanic soils of the Andes had about twice as much carbon as previously thought and that a significant proportion was stabilized as aluminium (Al)‐complexes. The latter mechanism was also found by Iamarino & Terribile () in Andic soils of the Italian mountains and by Hernández et al () in the soils of Tenerife. However, Scheel et al () attributed the decrease in C mineralization upon increase in soil Al concentration in forest soils to the reduced bioavailablity of C caused by precipitation rather than any toxic effect of the Al at low pH.…”
supporting
confidence: 74%
“…Hernández et al, 2012). However, Hernández et al (2012) found no significant relationships between the amorphous minerals and aromatic compounds. We consequently hypothesise that the dichromate treatment was not able to oxidise all organic fractions that were strongly bound to mineral surfaces.…”
Section: Chemical Oxidation Resistant Carbon (Corec Fraction)mentioning
confidence: 85%
“…Particularly in soils where allophanes are present, potentially easily biodegradable substances are strongly adsorbed or stabilised by complexation processes with amorphous surfaces and, consequently, protected against degradation and oxidation (see e.g. Hernández et al, 2012). However, Hernández et al (2012) found no significant relationships between the amorphous minerals and aromatic compounds.…”
Section: Chemical Oxidation Resistant Carbon (Corec Fraction)mentioning
confidence: 99%
“…On the other hand, the reactive mineral surface of organomineral complexes in the complex soil matrix (mainly the topsoil layer) could be greatly improved through organic amendments to soil, such as the anthropogenic importation of organic fertilizers under long-term experimentation (Schmidt et al, 2011;Hernandez et al, 2012;Yu et al, 2012;Wen et al, 2014a;Abdala et al, 2015). Based on a meta-analysis of 49 sites and 130 observations in the world, Maillard and Angers (2014) found that cumulative manure input had a dominant effect on SOC stock changes when compared to no fertilization and chemical fertilization (Maillard and Angers, 2014).…”
mentioning
confidence: 99%